2010
DOI: 10.1128/cvi.00423-09
|View full text |Cite
|
Sign up to set email alerts
|

Coincorporation of LpxL1 and PagL Mutant Lipopolysaccharides into Liposomes withNeisseria meningitidis Opacity Protein: Influence on Endotoxic and Adjuvant Activity

Abstract: Wild-type lipopolysaccharide (LPS) of Neisseria meningitidis normally contains six acyl chains. Pentaacylated LPS forms were generated through inactivation of the lpxL1 gene or through the expression of the Bordetella bronchiseptica pagL gene in N. meningitidis. The resulting LPS species, designated LpxL1 LPS and PagL LPS, respectively, display reduced endotoxic activity compared to wild-type LPS. Here, we determined the adjuvant potential of PagL LPS by comparison with the broadly used LpxL1 LPS. We also inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 44 publications
0
19
0
Order By: Relevance
“…However, the lpxL1 Ϫ LPS was more strongly reduced in its ability to activate human as compared with murine TLR4, as measured by the expression of the NF-B transcription factor and various MyD88-dependent cytokines (40). For PagL-deacylated meningococcal LPS, adjuvant activity has also been demonstrated in mice, but it should be noted that in this animal species there is very little difference in endotoxic activity compared with wild-type hexaacylated LPS (41). In this study, we have determined that the lpxL1 Ϫ -pentaacylated LPS structure containing a fully phosphorylated lipid A, as determined by MS analysis, at the concentrations used is unable to induce the production of not only MyD88-dependent cytokines (IL-6 and IL-10) but also of the TRIF-dependent chemokine IP-10 in human monocytic MM6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…However, the lpxL1 Ϫ LPS was more strongly reduced in its ability to activate human as compared with murine TLR4, as measured by the expression of the NF-B transcription factor and various MyD88-dependent cytokines (40). For PagL-deacylated meningococcal LPS, adjuvant activity has also been demonstrated in mice, but it should be noted that in this animal species there is very little difference in endotoxic activity compared with wild-type hexaacylated LPS (41). In this study, we have determined that the lpxL1 Ϫ -pentaacylated LPS structure containing a fully phosphorylated lipid A, as determined by MS analysis, at the concentrations used is unable to induce the production of not only MyD88-dependent cytokines (IL-6 and IL-10) but also of the TRIF-dependent chemokine IP-10 in human monocytic MM6 cells.…”
Section: Discussionmentioning
confidence: 99%
“…Considering on the one hand that Opa proteins can be effective targets for bactericidal antibodies [25,26], but on the other hand may suppress or at least decrease an effective immune response against OMV antigens by this inhibition of CD4 T cell proliferation, it is important to establish whether these in vitro observations are relevant for in vivo immunogenicity. Until now it has not been possible to answer this question by immunization experiments in mice or other animals because the Opa-CEACAM1 interaction is strictly species-specific.…”
Section: Introductionmentioning
confidence: 99%
“…We thus combined the two antigens in the same liposomes, with the aim of delivering them together to the same antigenpresenting cells and to study how this would affect immune responses. Although previous studies reported the coincorporation of meningococcal proteins with LOS into liposomes, with LOS acting as an adjuvant on antiprotein responses (3,4), none of these studies ever demonstrated that the meningococcal protein could act as an adjuvant on the anti-LOS response. Surprisingly, we found that rlip-TbpB was a potent adjuvant for anti-LOS responses when it was coformulated with LOS in liposomes, but we did not observe an adjuvant effect of LOS on the anti-TbpB response.…”
Section: Discussionmentioning
confidence: 93%